Approximate-analytic solution of hyperchaotic finance system by multistage approach - Rangkuti, Y.M.; Alomari, A.K.; Anakira, N.R.; A.F. Jameel, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper devotes to constructing an approximate analytic solution for the hyperchaotic finance model. The model describes the time variation of the interest rate, the investment demand, the price exponent, and the average profit margin. The multistage homotopy analysis method (MHAM) and multistage variational iteration method (MVIM) are utilized to generate the analytical solutions. The solutions are presented in terms of continuous piecewise functions without interpolation. These procedures prove their applicability for this kind of model due to rapidly convergent series solutions with easily computable terms, iterates, and efficiently obtained by applying it over multiple time intervals. We also provide the convergences theorem of the MHAM. Numerical comparisons are displayed with the results obtained by MHAM, MVIM, and the fourth-order Runge-Kutta method to demonstrate the validity and effectivity of this procedure.